Helicobacter pylori eradication induces marked increase in H+/K+-adenosine triphosphatase expression without altering parietal cell number in human gastric mucosa. Issue 2 (4th May 2005) - Osawa, H; Kita, H; Ohnishi, H; Hoshino, H; Mutoh, H; Ishino, Y; Watanabe, E; Satoh, K; Sugano, K
Abstract : Background and aims: Gastric acid secretion is downregulated by Helicobacter pylori infection and upregulated after its eradication, but the mechanisms are still unclear. We examined the effects of H pylori eradication on the number of parietal cells and on expression of molecules functioning in acid secretion in the human gastric mucosa. Methods: We enrolled 111 consecutive men with chronic gastritis induced by H pylori . Biopsy specimens were endoscopically obtained before and 12 weeks after successful eradication of H pylori and parietal cell numbers were counted. mRNA expression levels of H + /K + -adenosine triphosphatase (H + /K + -ATPase), anion exchanger 2, M3 muscarinic receptor, intrinsic factor, and interleukin 1β were determined with a real time reverse transcriptase-polymerase chain reaction method. The severity of gastric atrophy was evaluated using the serum pepsinogen I/II ratio. Results: No significant difference was observed in parietal cell numbers before and after H pylori eradication. Median mRNA expression levels of H + /K + -ATPase in the gastric mucosa increased 250-fold after H pylori eradication accompanied by attenuation of interleukin 1β. A large increase in H + /K + -ATPase expression was observed even in patients with severe atrophic gastritis. In contrast, fold increases in mRNA expression levels, including intrinsic factor, anion exchanger 2, and M3 muscarinic receptor, after eradication therapy, were limited to 1.4, 2.3, and 2.5 times, respectively. Conclusions: In the absence of alteration of parietal cell number, gastric H + /K + -ATPase mRNA expression was markedly restored after successful H pylori eradication, suggesting a central role for the restoration of H + /K + -ATPase expression in gastric acid secretion recovery after H pylori eradication.